please solve this question...
Attachments:
![](https://hi-static.z-dn.net/files/d11/05312a10646411e868ceff5ff33e76f3.jpg)
Answers
Answered by
0
solution is: 3a^2-12ab+12b^2-5a+10b
Attachments:
![](https://hi-static.z-dn.net/files/d6b/9a46c61bd291eb817ad2c8c368eb3779.jpg)
Answered by
0
Answer:
3a² - 5a - 12ab + 10b+ 12b²
Step-by-step explanation:
3(a - 2b)² - 5(a-2b)
(a-b)²=a²-2ab + b²
=3[(a)² - 2(a)(2b) + (2b)²] - 5a+10b
=3[a² - 4ab + 4b²] - 5a+10b
=3a² - 12ab + 12b² - 5a+10b
=3a² - 5a - 12ab + 10b+ 12b²
Hope Helpful For You mark me as brainliest
Similar questions
English,
3 months ago
English,
3 months ago
Math,
6 months ago
World Languages,
6 months ago
Hindi,
1 year ago